Occurrences and characteristics of forced marriages among girls married before the age of 16 in a Northern Nigerian State - Felix O. Sanni; Olumide F. Ajani; Elizabeth A. Sanni; Zachary T. Gwa; Michael O. Dada; Yemisi B. Alabi; Donald C. Udah; Jubril A. Kareem (MGM Journal of Medical Sciences)
Background: Child marriage is deeply ingrained in Nigerian tradition, culture, and religion, and the country has one of the highest rates of child marriage globally. The objective of this study was to examine the occurrence and characteristics of coerced marriages among girls married before turning 16 in Borno, Nigeria. It perceives premarital unions as a substantial violation of human rights, particularly affecting the independence of adolescent girls. Materials and Methods: This cross-sectional study took place in three local government areas (LGAs) situated in Borno, Nigeria, namely Konduga, Jere, and Maiduguri Metropolitan City LGAs. Structured questionnaires were distributed to 210 female participants aged between 15 and 49, who were married before reaching 16, from 1989 to 2019, to gather data. Data analysis was done using IBM Statistical Package for the Social Sciences version 25.0, headquartered in Chicago, Illinois, United States. Results: The incidence of forced marriage among girls under 16 years old was recorded at 23.8%, notably higher during the period spanning from 1980 to 1989 at 37.5%. Among respondents currently married, approximately one-fifth (23.1%) disclosed being coerced into marriage. A higher proportion underwent forced marriage during the ages of 9–12 years, accounting for 33.3%. Moreover, a considerable portion of respondents with no formal education (28.6%) and those who attended Qur’anic schools (25.5%) were compelled into marriage. The prevalence of fistula among girls married early stood at 8.6%, with 10.6% among those not subjected to forced marriage and 2.0% among girls who were coerced. Among early married girls, 20.5% reported facing ill-treatment from their spouses, with a higher proportion (30.0%) among those coerced into marriage compared to those not coerced (17.5%). Additionally, gender-based violence from family members was notably more prevalent among girls forced into marriage (32.0%), with a significance level of P < 0.05. Conclusion: Efforts directed toward reducing the prevalence of girl-child marriage in Nigeria should focus on tackling entrenched cultural norms that differ among ethnic groups and religious beliefs. The public health implications encompass gender-based violence, abuse, and the breakdown of marriages.